Historical significance of the Chinese Emperor’s Edict- Letter to the Kazakh Sultan, preserved in Chinese archives - Abdilashim Дүйсенәлі (Turkic Studies Journal, 2024)
On the basis of Chinese and other sources, the article considers the Edict- Letter of the Chinese Emperor of the Qing Dynasty to the Kazakh Khanqoja Sultan, the owner of the eastern border regions. According to Kazakh documents, the Kazakh Khans Abylai and Abilpeiz established official ties with the Qing Empire after the destruction of the Dzungars in 1757. Trade fairs were opened in Urumqi in 1758, in 1761 in Yili, and in 1764 in Tarbaghatai, thereby favorable conditions were created for the development of political and economic relations between the two sides. That is confirmed by mutual correspondence contributed to a significant increase of official documents. Most of these documents, preserved in Chinese archives, are letters from Kazakh Khans, which were delivered through ambassadors to the local administration of the Qing Empire, and then forwarded to the Emperor himself. The analyzed archival document is the Edict-Letter sent by the Qian Long Emperor to Khanqoja Sultan in 1787. The author of the article, exploring the language of the Chinese Emperor’s Edict-Letter to the Kazakh Sultan, reveals the history of interethnic relations between the countries, as well as the history of the Kazakh Khanate in the XVIII century.